Intracellular stored calcium plays a minor role in Gq-coupled receptor-mediated contraction in rat airway smooth muscle - Kayatri Govindaraju; Mei Kee Lee; Yvonne Mbaki; Ting Kang Nee (Life Sciences, Medicine and Biomedicine, 2018)
The general notion of activation of Gq-protein coupled receptors involves the mobilisation of stored and extracellular calcium and leads to smooth muscle tissue contraction. The aim of this study was to investigate the involvement of calcium mediated contractions in vascular and airway smooth muscles. Using the standard organ bath procedures, aortic and tracheal rings were obtained from 6 to 8 week-old male Sprague Dawley rats. To activate the Gq protein receptors, phenylephrine (PE), an α1-adrenoceptor agonist, and carbachol, a M3 cholinoceptor  agonist, was added to baths containing the aortic and tracheal rings, respectively.  The maximum response (Emax) to PE was reduced from 158.8 ± 11.8% (n=6) to 62.5 ± 12.4 % (n=8) upon removal of extracellular calcium in Krebs-Ringer solution. Maximal response to PE was also suppressed in the presence of nifedipine, a L-type Ca2+ channel inhibitor,  (70.3 ± 11 %, n=8) and SKF96365, a canonical transient receptor potential channel inhibitor, (26.7 ± 13.2 %, n=5) when the influx of extracellular calcium was blocked. Removal of stored calcium also attenuated the PE contraction (p<0.05). Contractile responses to carbachol in the airway were totally abolished in the absence of calcium in the Krebs-Ringer solution (208.6 ± 23 % [n=8] vs 10.7 ± 4.2 % [n=3]). This is different from the aorta where a measurable response was detected despite the absence of external calcium. Blockage of extracellular calcium influx in the presence of nifedipine and SKF96365 also showed similar lack of responses in trachea. Interestingly, removal of stored calcium did not affect the carbachol responses (p>0.05). From these observations, we conclude that the role of stored and extracellular calcium in Gq protein activation is not the same across different type of smooth muscle tissues.